SISTEM KERJA BURUH PELABUHAN DI TANJUNG UMA KECAMATAN LUBUK BAJA KOTA BATAM - Yusniati "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The working system is a system of unity, the way, setting and implementation of the procedure work so it can be with the right completing a job. this research is about The Work System of the laborers in the Tanjung Uma anchorage district of Lubuk Jaya Batam City". The location of this research is precisely in the political district administered by a village chief of Tanjung Uma district Lubuk Baja Batam City. This study aims to analyze how system of the laborer and what the factors that affect income or wages trade work laborers in the Tanjung Uma anchorage. This research used qualitative method with the type of descriptive data in the form of the writtenword or verbal and explained reasoning data through reasoning based on the logic to draw the conclusion that logical about the data analyzed so it can be described a situation in a systematic way in accordance with the phenomena researched. Technique collecting data use a technique observation, interview and documentation. Based on the results of research loading and discharging workers Tanjung Uma anchorage have a system of the rules of the work consists of two of the working group named group A and B, consists of two shift ( setting work ) morning and evening, 1 shift is 12 hours, consisting of 3 days day shifth , 2 days night shift,and 1 day off with the system of wages paid every 1 days but the results of that work will be shared after 3 days. they work depends on there or not on the ship toward the anchorage, automatically the income of the laborers becomes lower and uncertain because it was just expecting to revenue from the results of how much of loading and discharging goods from the ship. As for several factors that influence the system of the laborer’s working system is income, there is or not the ship, the system rolling and overworking.Keywords : work system of the laborers, work setting, there is or not the ship.